2019
DOI: 10.3390/jcm8101692
|View full text |Cite
|
Sign up to set email alerts
|

Liver Grafts with Major Extended Donor Criteria May Expand the Organ Pool for Patients with Hepatocellular Carcinoma

Abstract: The major extended donor criteria (maEDC; steatosis >40%, age >65 years, and cold ischemia time >14 h) influence graft and patient outcomes after liver transplantation. Despite organ shortages, maEDC organs are often considered unsuitable for transplantation. We investigated the outcomes of maEDC organ liver transplantation in patients with hepatocellular carcinoma (HCC). Two hundred and sixty-four HCC liver transplant patients were eligible for analysis. Risk factor analysis was performed for early allograft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
3
12
0
1
Order By: Relevance
“…This clearly suggests that with the increase of the MELD score, the tolerance of prolonged cold ischemia decreases. Because allocating grafts with longer CIT to the aforementioned recipient category did not carry disproportionate risk, this type of matching (longer CIT with HCC recipients and MELD < 20) is in line with previous findings and may be acceptable when facing organ shortage (2,5). Patient survival constantly better than graft survival, also after longer CIT, was observed only in recipients with HCC.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…This clearly suggests that with the increase of the MELD score, the tolerance of prolonged cold ischemia decreases. Because allocating grafts with longer CIT to the aforementioned recipient category did not carry disproportionate risk, this type of matching (longer CIT with HCC recipients and MELD < 20) is in line with previous findings and may be acceptable when facing organ shortage (2,5). Patient survival constantly better than graft survival, also after longer CIT, was observed only in recipients with HCC.…”
Section: Discussionsupporting
confidence: 85%
“…This may be attributed to the higher resilience of a re-transplant in patients with HCC. While Goldaracena et al showed that patients with high labMELD scores benefit from transplantation as soon as possible and irrespective of the organ quality, our two recent studies pointed out that exact match between graft and recipient is important, and that grafts with maEDC could be allocated to low-risk patients with labMELD <20 e.g., patients with HCC (2,5,22). These findings were confirmed in a recent large cohort CTS study (8).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations